2009
DOI: 10.1097/hjh.0b013e328324ed86
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-dependent relaxation factor released by perivascular adipose tissue

Abstract: Ang-(1-7) released by PVAT acts on the endothelium to cause the release of nitric oxide, and nitric oxide acts as a hyperpolarizing factor through K(Ca) channels to cause relaxation of the blood vessel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
1
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(111 citation statements)
references
References 46 publications
3
93
1
10
Order By: Relevance
“…ADRF is not adiponectin 10 and does not involve functional leptin receptors. 1 Lee et al 34 identified Ang 1-7 as perivascular derived relaxing factor; however, the effects of Ang 1-7 are mediated via both endothelium and BK channels and not by K v channels. 34 Both findings indicate that Ang 1-7 is not ADRF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ADRF is not adiponectin 10 and does not involve functional leptin receptors. 1 Lee et al 34 identified Ang 1-7 as perivascular derived relaxing factor; however, the effects of Ang 1-7 are mediated via both endothelium and BK channels and not by K v channels. 34 Both findings indicate that Ang 1-7 is not ADRF.…”
Section: Discussionmentioning
confidence: 99%
“…1 Lee et al 34 identified Ang 1-7 as perivascular derived relaxing factor; however, the effects of Ang 1-7 are mediated via both endothelium and BK channels and not by K v channels. 34 Both findings indicate that Ang 1-7 is not ADRF. Furthermore, methyl palmitate was reported as a novel candidate for periadventitial vasoregulation in the rat aorta.…”
Section: Discussionmentioning
confidence: 99%
“…Perivascular Adipose Tissue (PVAT) is an ectopic fat depot which plays an important role in regulating vascular function. PVAT exerts a anticontractile effect in both rats and humans [5][6][7] through an endothelium-dependent mechanism which involves transferable factors such as leptin [8] or angiotensin [7,9] and through an endothelium-independent mechanisms involving H 2 O 2 [10], H 2 S [11], NO [12], or palmitic acid methyl ester [13]. The above-mentioned phenomenons can be altered under pathophysiological conditions.…”
Section: Isolated Aortic Ring Studiesmentioning
confidence: 99%
“…Gao et al [4] reported a dual mechanism for the anti-contractile effects, one that involves an endothelium-dependent relaxation via NO release and subsequent K Ca channel activation, and the other involving an endothelium-independent mechanism via H 2 O 2 and subsequent release of soluble guanylate cyclase [7] . More recently, the adipocyte-derived relaxation factor (ADRF)-induced endothelium-dependent relaxation via NO release has been identified to be Ang-(1-7) [8] . Nonetheless, the physiological significance of finding in such in vitro study in the interaction between ADRF and EDRF from across the entire thickness of the vessels wall in vivo remains vague at large.…”
Section: Perivascular Adipocytes: Diffusible Factors and Control Of Vmentioning
confidence: 99%